RETRACTED: COVID-19 as an “Infodemic” in Public Health: Critical Role of the Social Media - Banerjee, Debanjan; Meena, K. S. (Frontiers in Public Health, 2021)
The Coronavirus disease 2019 (COVID-19) pandemic has emerged as a significant and global public health crisis. Besides the rising number of cases and fatalities, the outbreak has also affected economies, employment and policies alike. As billions are being isolated at their homes to contain the infection, the uncertainty gives rise to mass hysteria and panic. Amidst this, there has been a hidden epidemic of “information” that makes COVID-19 stand out as a “digital infodemic” from the earlier outbreaks. Repeated and detailed content about the virus, geographical statistics, and multiple sources of information can all lead to chronic stress and confusion at times of crisis. Added to this is the plethora of misinformation, rumor and conspiracy theories circulating every day. With increased digitalization, media penetration has increased with a more significant number of people aiding in the “information pollution.” In this article, we glance at the unique evolution of COVID-19 as an “infodemic” in the hands of social media and the impact it had on its spread and public reaction. We then look at the ways forward in which the role of social media (as well as other digital platforms) can be integrated into social and public health, for a better symbiosis, “digital balance” and pandemic preparedness for the ongoing crisis and the future.